Expression of hippocampal brain-derived neurotrophic factor and its receptors in Stanley consortium brains - Dunham, Jason S.; Deakin, J. F. William; Miyajima, Fabio; Payton, Tony; Toro, Carla Tatiana (Elsevier Science B.V., Amsterdam., 2009)
Several lines of evidence implicate BDNF in the pathophysiology of psychiatric illness. BDNF polymorphisms have also been associated with the risk of schizophrenia and mood disorders. We therefore investigated whether levels of (pro)BDNF and receptor proteins, TrkB and p75, are altered in hippocampus in schizophrenia and mood disorder and whether polymorphisms in each gene influenced protein expression. Formalin-fixed paraffin-embedded hippocampal sections from subjects with schizophrenia, major depressive disorder (MDD), bipolar disorder (BPD) and non-psychiatric controls were obtained from the Stanley Foundation Neuropathology Consortium. (pro)BDNF, TrkB(T1) and p75 protein densities were quantified by immunoautoradiography and DNA extracted from each subject was used to determine the effect of genotype on protein expression. In MDD, reductions in (pro)BDNF were seen in all layers of the right but not the left hippocampus with no changes in the dentate gyrus. The pattern was similar but less marked for BPD. In addition, BPD but not MDD patients, had bilateral reductions in p75 in hippocampal layers but not in dentate gyrus. No changes in TrkB(T1) density were seen in any diagnosis. These findings suggest MDD and BPD may share impairment in (pro)BDNF expression. However, BPD may involve impairments of both (pro)BDNF and p75 receptor, whereas MDD may involve impaired (pro)BDNF alone. Moreover, the lateralisation of changes may indicate a role of asymmetry in vulnerability to MDD. Hippocampal (pro)BDNF and receptor levels were also affected by genotype, suggesting that allelic variations are important in the hippocampal abnormalities seen in these psychiatric disorders.
Keywords: Neurotrophin; Expression; Polymorphism; Postmortem; Schizophrenia; Mood disorders